REAGEN BUATAN SENDIRI SEBAGAI REAGEN ALTERNATIF UNTUK PEMERIKSAAN KADAR ALBUMIN - Fusvita Merdekawati (Meditory : The Journal of Medical Laboratory, 2019)
The use of homemade reagents is a modification of the inspection method that has been validated, so that to be used it needs to be tested first for its quality in order to obtain a guarantee of quality against the results of a good examination The study aimed to determine the performance of homemade reagents compared to using a commercial reagent kit on albumin examination. The research method is descriptive with comparative studies where commercial reagent kits act as a comparison method and homemade reagents act as test methods. Both of these reagents are in the form of a solution. Homemade reagents are used for albumin examination in the validation test method which consists of test accuracy, precision, linearity, reportable range, limit detection, limit quantity, recovery, and interference. The data obtained is then processed using descriptive statistical tests, One Way Annova and Wesgard rules. Based on the results of testing, all parameters in the method validation were accepted, so there was no difference in performance between using homemade reagents and commercial reagent kits